Implementation of Good Corporate Governance in Preventing Fraud in Islamic Banking - Hendra, Joni; Anggraini, Cindy; Amini, Zakiyah; Nurhidayah, Putri; Hidayatunnisa, Hidayatunnisa (CV. Rayyan Dwi Bharata, 2025)
Islamic banking is a rapidly growing financial sector in Indonesia, along with increasing public awareness of the financial system based on Islamic sharia principles. Despite having a strong ethical foundation, Islamic banking still faces serious challenges, especially in terms of fraud risk. Fraud in the banking world can be in the form of abuse of authority, manipulation of financial reports, and producer deviations that can harm customers and the institution as a whole. This study aims to analyze the role of Good Corporate Governance (GCG) in preventing fraud in the Islamic banking sector. GCG is a corporate governance system that focuses on the principles of transparency, accountability, responsibility, independence, and fairness in order to create effective, efficient, and ethical management. The research method used is a literature study by reviewing various literature such as books, journals, and relevant documents. The results of the study show that the implementation of GCG as a whole can minimize the opportunity for fraud through strengthening the internal supervision system, increasing transparency of reporting, and optimizing the role of the Sharia Supervisory Board and an independent audit committee. With strong GCG, Islamic banking can increase public trust, strengthen institutional integrity, and support the sustainable growth of the Islamic financial sector. Therefore, the implementation of GCG is not only a compliance requirement, but also a strategic need in maintaining the stability and reputation of Islamic banking in Indonesia.